2022
DOI: 10.1038/s41591-022-01704-7
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing antibodies against the SARS-CoV-2 Omicron variant BA.1 following homologous and heterologous CoronaVac or BNT162b2 vaccination

Abstract: This is a PDF file of a peer-reviewed paper that has been accepted for publication. Although unedited, the content has been subjected to preliminary formatting. Nature Medicine is providing this early version of the typeset paper as a service to our authors and readers. The text and figures will undergo copyediting and a proof review before the paper is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

52
301
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 339 publications
(381 citation statements)
references
References 17 publications
52
301
0
1
Order By: Relevance
“…A RNA vaccine BioNTech-Pfizer (BNT162b2) and an inactivated whole virus vaccine CoronaVac are two of the most widely used COVID-19 vaccines globally, each with over 2 billion doses delivered so far 7 . We and others have shown that Omicron BA.1 is poorly neutralized by sera from individuals vaccinated with two doses of the BNT162b2 or CoronaVac 8,9 . A third dose of BNT162b2 vaccine was shown to increase neutralizing antibody titres in those previously vaccinated with two doses of BNT162b2 as well as in those vaccinated with CoronaVac.…”
Section: Textmentioning
confidence: 71%
See 4 more Smart Citations
“…A RNA vaccine BioNTech-Pfizer (BNT162b2) and an inactivated whole virus vaccine CoronaVac are two of the most widely used COVID-19 vaccines globally, each with over 2 billion doses delivered so far 7 . We and others have shown that Omicron BA.1 is poorly neutralized by sera from individuals vaccinated with two doses of the BNT162b2 or CoronaVac 8,9 . A third dose of BNT162b2 vaccine was shown to increase neutralizing antibody titres in those previously vaccinated with two doses of BNT162b2 as well as in those vaccinated with CoronaVac.…”
Section: Textmentioning
confidence: 71%
“…The Omicon subvariant BA.2 virus (hCoV-19/Hong Kong/VM22000135_HKUVOC0588P2/2022) isolated in Hong Kong on 3 rd January 2022 was used for this study (GISAID EPI_ISL_9570707). The PRNT50 and PRNT90 data with the BA.2 virus derived from this study was compared with PRNT50 and PRNT90 data obtained for Omicron subvariant BA.1 and ancestral virus obtained for the respective sera previously reported (8) .…”
Section: Methodsmentioning
confidence: 96%
See 3 more Smart Citations